Optimal design of a three phase magnetic flux leakage transformer for industrial microwave generators - Hamid Outzguinrimt; Mohammed Chraygane; Mouhcine Lahame; Rajaa Oumghar; Ali Bouzit; Mohammed Ferfra (Institute of Advanced Engineering and Science, 2020)
This paper aims to get an optimal high voltage magnetic flux leakage transformer design of a three-phase shell type. Optimal design of transformer requires determination of design variables to optimize a particular objective and satisfying a set of constraints. The objective function is to minimize the total mass and reduce the volume of the transformer. This function depends on inputs, which are divided into optimization variables. Each optimization variable varies within a certain interval thus defining a global search space. It is within this space that we seek the optimal solution. The constraints: maximum and average current of magnetron anode are part of the problem in order to limit the overall search space. The results obtained indicate that the method has provided a global optimum. The computation time and cost of active material are much reduced compared with the conventional design results.